2014
DOI: 10.1111/cobi.12304
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of the Effects of Forest Fragmentation on Interspecific Interactions

Abstract: Forest fragmentation dramatically alters species persistence and distribution and affects many ecological interactions among species. Recent studies suggest that mutualisms, such as pollination and seed dispersal, are more sensitive to the negative effects of forest fragmentation than antagonisms, such as predation or herbivory. We applied meta-analytical techniques to evaluate this hypothesis and quantified the relative contributions of different components of the fragmentation process (decreases in fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
121
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(147 citation statements)
references
References 46 publications
9
121
7
Order By: Relevance
“…There is considerable debate in ecology concerning the effects of land use changes, including vegetation loss and fragmentation on assemblage and community structure and function (e.g. Allan, ; Laurence et al ., ; Magrach et al ., ). Dragonflies have been used as a focal group in these debates (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…There is considerable debate in ecology concerning the effects of land use changes, including vegetation loss and fragmentation on assemblage and community structure and function (e.g. Allan, ; Laurence et al ., ; Magrach et al ., ). Dragonflies have been used as a focal group in these debates (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…These changes could physiologically stress arboreal species in fragmented habitats, and cause trees to promote more frequent flowering, fruiting (Aldrich and Hamrick 1998), leaf production (Lovejoy et al 1986, Sundarapandian andSwamy 1999) and leaf shedding (Sizer and Tanner 1999). For example, Magrach et al (2014) indicated that some plant species show compensatory responses to habitat fragmentation involving demographic effects, and changes in plant defenses and regrowth rates. Alternatively, fragmentation may confer benefits; for example, isolated trees are free of competition from neighboring conspecifics or other species.…”
Section: Fragmentation and Host Plant Qualitymentioning
confidence: 99%
“…Despite the extensive scientific literature measuring fragmentation-induced effects on species and communities (Fahrig 2003;Lindenmayer and Fischer 2006), the role of interspecific interactions in shaping fragmented populations is still far from clear (Amarasekare 2003;Magrach et al 2014). Several theoretical studies describe possible mechanisms regulating the coexistence or exclusion of species in modified landscapes, but empirical confirmation is limited and based on indirect inference (Chesson 2000;Amarasekare 2003;Boeye et al 2014).…”
Section: Introductionmentioning
confidence: 99%